Analisis Sumber Belajar Cetak IPA dalam Mengatasi Kesulitan Belajar Siswa Kelas 4 SDN Periuk Jaya Tangerang - Ismawanti, Agnes; Putri, Disa Cahaya; Azzahra, Fernita Dwi; Magdalena, Ina; Nurvitasari, Nurvitasari (Lembaga Yasin AlSys, 2023)
Learning is assistance provided by educators so that the process of acquiring knowledge and knowledge, mastering skills and character, and forming attitudes and beliefs in students can occur. In learning activities, of course there are other components to support these learning activities, namely learning resources. There are many science learning resources that teachers can use in learning activities that are in accordance with the teaching material. However, there are several obstacles faced by students with the learning resources they use, such as those commonly used are printed learning resources. In this case, a teacher needs to develop printed learning resources in order to overcome the difficulties faced by students in their learning activities. This study aims to find out how teachers develop science print learning resources for grade 4 students at SDN Periuk Jaya Permai. The type of this research is observation, interview guide and researcher as instrument and key. The source of the data for this research is the results of interviews with teachers at the SDN. The result of this research is that teachers need to develop printed learning resources according to their creativity, such as being able to add pictures to power points or even draw using a blackboard.